Hm-corrbreak: an alternative new material for corrosion inhibitors formulation from harumanis peel / Nur Aina Radin Sukimi ... [et al.] - Radin Sukimi, Nur Aina; Yahya, Solhan; Alias, Nurul Zawani (2022)
The use of natural resources as corrosion inhibitors has been the most frequent research conducted by scientists, owing to its significant effect in preserving the metal integrity, “green” and organic-based as well as environmentally friendly. In this study, local mango waste (Harumanis peel) was proven to be a good corrosion inhibitor for mild steel in an acidic medium. The crude peel extract was subjected to the immersion test in 1 M HCl to evaluate the potential of the waste as a corrosion inhibitor. The results indicate that the peel extract inhibits mild steel corrosion up to 98% efficiency while mangiferin gives about 96% efficiency. It also shows that the rise in inhibitor concentration for both peel and mangiferin caused an increase in the corrosion inhibition efficiency of the mild steel. The corrosion rate of the mild steel was reduced from 0.0023 to 0.0015 mm/y as the amount of the peel extract increased from 2 x 10-decreased due to the interaction of significant chemical constituents present in the peel extract, thus reducing the metal dissolution. The chemical constituents and various functional groups in the peel extract as well as the heterocyclic structure of mangiferin were the main properties of the anticorrosive agent for corrosion control.